Western Academic Insight of Islam and its Prophet: A Critical Reading to the Writings of Watt, Norman, and Considine - Al-Olaqi, Fahd Mohammed Taleb Saeed (Journal of Al-Tamaddun, 2025)
There has been a gradual change in the Western academic stand toward developing scholarly approaches to investigate Prophet Muhammad’s Islamic mission to the world. Early Western Orientalists presented Prophet Muhammad as a mistaken person to the founder of Islam and antichrist, but this is continually refined by academic advancement. Although Europeans now have a more realistic view of Islam and its Prophet, some historical biases persist, such as the portrayal of Thomas Carlyle for Prophet Muhammad as a world leader or hero. However, his true nature as a divine messenger is entirely missed or denied. Watt, Norman, and Considine examined, sorted, and proved some distorted reports. These academic experts advanced their approaches to understanding Prophet Muhammad’s manners. They acknowledged the reflection of a European prejudice toward the Western material about Islam and its Messenger. More hard work is required to narrow the gap of misunderstanding between Islam and The West.